Strategies for teaching business writing in higher education (on English language material) - Jojua, Tamar; Daraselia, Maia (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The global social and economic changes have intensified the close personal and business contacts between the representatives of different countries. In today’s world the number of people who are traveling abroad on private or business issues are growing. Accordingly, it is not surprising, that there is a pressing need for such employees who with their high professional skills can communicate fluently in English. In today’s competitive job market one of must-have Skills is undoubtedly, the effective skill for business correspondence. All types of business correspondence-letters, email messages, faxes, memos, CVs, resumes, reports, minutes and many other documents must be tailored in a proficient, comprehensive, and informative way.In the process of formation professionally oriented foreign language skills it is necessary, that teaching process should be based on really motivating, interesting and stimulating activities. The article gives the detailed analysis of the role and importance of modern teaching approaches (Task-based and student-oriented) and strategies in the process of teaching business writing to EFL students. Some models of professionally oriented techniques and drills are illustrated in the given article.